P832 Effectiveness of the quadrivalent HPV vaccine against HSIL and CIN: a data-linkage study. (14th July 2019) - Donken, Robine; Albert, Arianne; Sarai Racey, C; Smith, Laurie; Niekerk, Dirk Van; Spinelli, John; Pedersen, Heather; Krajden, Mel; Naus, Monika; Masaro, Cindy; Dawar, Meena; Sadarangani, Manish; et al.
Abstract : Background: Although originally approved for three-doses, two doses of the HPV vaccine are now approved for 9–14 year olds in British Columbia (BC), Canada. Post-hoc analyses have shown similar efficacy compared to three-doses even after one-dose. Vaccinated cohorts that include incompletely vaccinated individuals offer the opportunity to evaluate the effectiveness of reduced dosing schedules. We aimed to estimate effectiveness of one-dose of quadrivalent vaccine against high-grade squamous intraepithelial lesion (HSIL) and cervical intraepithelial neoplasia grade 2 or higher (CIN2+). Methods: Data-linkage was performed between the population-based Cervical Cancer Screening Program and immunization registries in BC. Occurrence of HSIL and CIN2+ were compared in a screening cohort of YW born between 1994–2005 who were either (a) unvaccinated; (b) completely vaccinated per-schedule (2-doses 150 days apart or 3-doses) between 9–14 years of age; or (c) vaccinated between 9–14 years of age with one-dose. Relative incidence rates (RR, (95%CI)) were calculated using Poisson regression and adjusted for birth year and age at first screening. Results: Overall, 19, 496 women were unvaccinated, 14, 130 were completely vaccinated (mean age at vaccination 13.3±1.2), and 471 vaccinated with one dose only (mean age at vaccination 13.4±1.1). We found significant protection among completely vaccinated compared to unvaccinated women. The adjusted RR for HSIL was 0.52 (0.43–0.64) and for CIN2+ 0.42 (0.31–0.57). No significant protection after one dose against HSIL and CIN2+ was observed compared with unvaccinated women, respective adjusted RR 0.69 (0.27–1.41) and 1.21 (0.43–2.86). Conclusion: In this observational study, no evidence of protection of one-dose against HSIL and CIN2+ was observed, while protection was found amongst completely vaccinated. The small sample size and the potential for administrative data biases may have impacted this preliminary analysis. This methodological approach provides a platform for further analyses, with larger numbers, to determine the potential impact of single dose HPV vaccination. Disclosure: No significant relationships.